The Limitations of the Principle of State Responsibility in the Global Climate Change Regime - Fajrin, Fera Wulandari; Larasati, Kandi Kirana; Tombi, Johan Tri Noval Hendrian; Luthfan, Gusti Fadhil Fithrian (Faculty of Law, Universitas Jambi, 2025)
Background: The global climate crisis, driven by increasing carbon emissions, has emerged as one of the most pressing challenges in international law. Despite significant milestones such as the Kyoto Protocol and the Paris Agreement, enforcement remains weak due to their reliance on soft law mechanisms. This issue deserves scholarly attention because it raises fundamental questions about state responsibility and the effectiveness of international environmental law in addressing climate change. Methodology: This research employs a doctrinal legal approach combined with a conceptual analysis. This method was selected to critically examine the normative gaps within the texts of international agreements, specifically how